ANALISA SISTEM PENYEDIAAN AIR BERSIH DI KECAMATAN NARMADA - I GEDE KEMULANDANA; MUHAMAD YAMIN; AMINULLAH AMINULLAH; TJOK ISTRI WIDYANI UTAMI DEWI SUDIRA (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
The provision of clean water is currently a problem in the services of PT. The Giri Wins Drinking Water Company (perseroda) in the Narmada District. The need for clean water is increasing every year while water sources are very limited. To anticipate the shortage of water discharge, it is necessary to find a source of raw water to meet the long-term needs in the service area. The purpose of this study was to determine the availability of water discharge in Narmada district and the need for clean water in Narmada district. The data analysis technique in this study used the Epanet 2.0 program. Researchers calculated the need for clean water for the service area of PT. Drinking Water Drinking Water Giri Menang (perseroda) and analyzing the availability of clean water in Narmada District by referring to secondary data in 2020 and taking a momentary discharge from the Suranadi water source.The results of the analysis show that the need for clean water for services in Narmada District up to the next 5 years projection is 138.21 lt/sec or 11,941,140 lt/hr. Meanwhile, the availability of clean water that can be utilized is 98 lt/sec or 8,491. 392 lt/day from 252 lt/sec or 21,772,800 lt/day available raw water